Poems of 1820 - Keats, John (Saga Egmont, 2022)
\'Poems of 1820\' is a great reminder that some achieve greatness at an early age. John Keats was 24 when this collection of poems was published and it is wild, ecstatic, sensuous and thrilling. In classic Romantic style, he uses Greek mythology and pagan imagery in his poetry and veers from explosive short poems to sprawling epics. Both - and much more in-between - appear in this collection, which is a poignant reminder of what the literary world missed when he died at the age of 25. This is ideal reading for fans of the poets Lord Byron and Percy Bysshe Shelley.